Dietary anhydrous milk fat depletes essential fatty acids in wistar rats which can be corrected by blending with linoleic acid rich sunflower oil - Belur, Lokesh Ramaswamy (Indian Journal of Dairy Science, 2014)
ABSTRACT: Anhydrous milk fat (AMF) is highly valued for its medicinal properties. AMF as sole source of fat in the diet exhibit hypocholesterolemic effect, but it also depletes the essential fatty acid level in the body. In order to maintain the essential fatty acid level in the body without affecting the hypocholesterolemic effect of AMF, blends of AMF with incremental amount of SFO was fed to rats. The control rats were fed with 20%SFO, and the treatment groups were fed with 20%AMF and AMF blended with SFO at 5%, 10% and 15% levels. Rats fed AMF at 20% levels showed 15% decrease in total cholesterol, 21.2% decrease in LDL cholesterol and 15% decrease in triacylglycerols as compared to rats fed 20% SFO. However, AMF fed rats also showed 35% decrease in linoleic acid levels in serum and 31% decrease in liver as compared to rats given SFO. Rats given AMF blended with incremental amount of SFO showed increase in the linoleic acid levels in serum and liver lipids, but serum and liver cholesterol level was found to be similar to that observed in rats given SFO. Therefore, blending of AMF with SFO helps in maintaining essential fatty acid levels in rats without compromising cholesterol lowering ability of AMF.